Kedudukan Purchase Order (PO) Sebagai Perikatan Dalam Sengketa Wanprestasi di Era Digital: Analisis Terhadap Praktik Transaksi Elektronik dan Kepastian Hukum di Indonesia - Aisyah Sahputri; Apri Amalia; Khaila Fibri Al Varzel; Chamelia Rambe; Febry Yana; Suma Guswani Br Pandia; Dewi Sartika Sari Nst; Said Maulana Hamzah (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This article examines the legal position of Purchase Order (PO) as a contractual obligation in disputes over default in Indonesia’s digital era. The increasing use of electronic transactions, especially through email, WhatsApp, and digital business platforms, has caused uncertainty regarding whether a PO can be treated as a binding agreement and used as a legal basis for a claim of breach of contract. The objective of this study is to analyze the legal status of PO in the context of Indonesian contract law, assess its validity when formed through electronic media, and evaluate the certainty of law in judicial practice. This research employs a normative juridical method with statutory, conceptual, and case approaches. The findings show that a PO may serve as a binding legal instrument when it reflects the elements of agreement, object, and lawful cause as required under Article 1320 of the Civil Code, and when the communication evidences clear consent between the parties. However, ambiguity remains when PO is exchanged informally through electronic platforms without explicit acceptance or a formal signature. Although the Electronic Information and Transactions Law supports the evidentiary value of electronic documents, the absence of uniform standards in judicial interpretation still creates legal uncertainty. Therefore, clearer regulatory and jurisprudential guidelines are needed to strengthen the legal certainty of PO in digital commercial transactions.